THE IMPACT OF WORK MOTIVATION AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE AT PT SINAR USAHA CEMERLANG, JAKARTA PUSAT - Randhy Agusentoso; Hasudungan Pangaribuan; Jaenudin Jaenudin (Asosiasi Dosen Muda Indonesia, 2025)
This study examines the influence of work motivation and work environment on employee performance at PT Sinar Usaha Cemerlang. Using a quantitative approach, the research analyzes data from a population of 65 employees, all of whom were included as the research sample through a saturated sampling technique. The study aims to determine how these two factors contribute to employee productivity, efficiency, and job satisfaction. The findings indicate that both work motivation and work environment have a significant positive impact on employee performance. Employees who feel valued, motivated, and work in a supportive environment tend to perform better, whereas those who experience a lack of recognition, poor work conditions, and ineffective communication demonstrate lower productivity. The study also reveals that the company needs to improve its reward system, career development programs, and workplace facilities to enhance employee engagement. Strengthening leadership support and internal communication is also crucial. Overall, the results suggest that PT Sinar Usaha Cemerlang should implement strategies that focus on workplace improvement and employee motivation to ensure sustained growth and organizational success.